2023
DOI: 10.32604/cmes.2023.024036
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Drug Concentration in Blood through Caputo-Fabrizio and Caputo Fractional Derivatives

Abstract: This study focuses on the dynamics of drug concentration in the blood. In general, the concentration level of a drug in the blood is evaluated by the mean of an ordinary and first-order differential equation. More precisely, it is solved through an initial value problem. We proposed a new modeling technique for studying drug concentration in blood dynamics. This technique is based on two fractional derivatives, namely, Caputo and Caputo-Fabrizio derivatives. We first provided comprehensive and detailed proof o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Recent reviews of several results of hybrid-type FDEs can be found in [17][18][19][20][21][22][23][24]. In this research, we investigate the existence of the solution to the fractional boundary value problem (BVP) hybrid-type:…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews of several results of hybrid-type FDEs can be found in [17][18][19][20][21][22][23][24]. In this research, we investigate the existence of the solution to the fractional boundary value problem (BVP) hybrid-type:…”
Section: Introductionmentioning
confidence: 99%